MOTIVASI INDIA MENGUNDURKAN DIRI DARI REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) TAHUN 2019 - Ika Annisa Putriani; Yessi Olivia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research aims to explain India’s decision to pull out from the Regional Comprehensive Economic Partnership (RCEP). RCEP is a regional free trade agreement consisted of 16 members included ASEAN members, Australia, New Zealand, Japan, South Korea, Russia, and India which is expected to be world’s biggest trading bloc. India involved in the RCEP negotiation in 2012 under the administration of Prime Minister Manmohan Singh but when Narendra Modi took over from Singh in 2014, India decided to withdraw from RCEP. This move has contradicted India’s Act East foreign policy to engage Asia-Pacific countries, which India could have beneffited from the participation in the RCEP.This research applies the economic nationalism perspective to analyze India’s decision to pull out from RCEP. According to this approach, some nationalists consider the safeguarding of national economic interests as the minimum essential to the security and survival of the state. This qualitative research uses explanative methods. The data was collected through document analysis or analysing the secondary data, such as book, journal, official publication, report and websites.This research finds that the decision to withdraw from RCEP has been driven from India’s domestic politics. Modi’s political party, Bharatiya Janata Party, and Modi viewed RCEP doesn’t reflect both India’s national and economic interest. There is also the concern that RCEP would threaten India’s domestic industries, especially the dairy and steel sectors which are very important in India. Keywords: India, Regional Comprehensive Economic Partnership, national interest, economic nationalism, and Modinomics.